Kajian Literatur Tuntutan Hak Tenaga Kerja Pariwisata Di Indonesia - Zaki Alif Ramadhani; Seprina Yana Alidha; Alhilal Furqan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Tourism is one of the sectors that contribute to the absorption of the national workforce where tourism absorbed around 10% of the national workforce in 2019. Tourism labor has natural rights that are already attached to it. The fulfillment of workers' rights can help workers in feeling self-esteem and dignity, feeling freedom and security during work, and having the opportunity to choose and carry out productive work without restrictions. Labor rights are based on human rights derived from a set of assumptions of moral theories of the intrinsic value of human beings assessed for their status as human beings regardless of certain historical, religious, or cultural abilities. This research uses a qualitative approach with literature analysis methods and inductive content analysis using secondary data based on 14 previous studies that discuss tourism labor rights in Indonesia from 2016 to 2021 obtained from several journals published online. The conclusions of this study show that the labor rights demanded include: 1) living wages, 2) social security, 3) protection of women and children, 4) working hours and leave, 5) benefits (fixed and non-fixed), 6) termination of employment (layoffs), 7) overtime and overtime pay 8) gender equality, and 9) training and certification. Tourism labor unions can function and play a role in the protection and enforcement of tourism labor rights.